The first Team Haemophilia Education meeting, 2015, Amsterdam, The Netherlands. (7th June 2016) - Berntorp, Erik; Hart, Daniel; Mancuso, Maria Elisa; d'Oiron, Roseline; Perry, David; O'Mahony, Brian; Kaczmarek, Radoslaw; Crato, Miguel; Pasi, John; Miners, Alec; Carlsson, Katarina Steen; Kitchen, Steve; et al.
Abstract: Haemophilia remains a complex disorder to diagnose and manage, requiring close cooperation between multidisciplinary healthcare professionals. There are still many unmet challenges in haemophilia care. The first Team Haemophilia Education (THE) meeting, held on 7–8 May 2015 in Amsterdam, The Netherlands, aimed to promote the optimal care of haemophilia patients through education of the multidisciplinary treatment team. This was achieved by reviewing the latest developments in haemophilia management, considering how these can be implemented in the clinic to improve patient care and providing a platform for networking and debate for all haemophilia treatment team members. Haemophilia treatment centres from several countries were asked to complete a premeeting online questionnaire to establish the biggest challenges that they face when managing patients. The concerns expressed were used to develop the agenda, which comprised a combination of formal presentations, case studies and informal workshops covering such topics as pharmacokinetics, laboratory assays and tailoring of treatment to individual patients. This report is a summary of the key developments in haemophilia care presented by various investigators and healthcare professionals at THE meeting 2015.